STAD MODEL APPLICATION TYPE OF COOPERATIVE IN EFFORTS TO INCREASE STUDENT LEARNING ACHIEVEMENT AND ACTIVITIES IN CLASS D VIII SUBJECT IN GEOGRAPHY LESSON SMP BHAKTIYASA SINGARAJA YEAR 2005/2006 - I Made Suasta (Media Komunikasi Geografi, 2015)
ABSTRACTThis research was held in SMP Bhaktiyasa Singaraja which it was aimed at investigates the students’ mastery and the students’ activity through cooperative method types Student Teams achievement Division (STAD). The data will be collected using test and observation sheet. Observation was used in investigation students’ mastery in Geography learning. And then the data will be analyzed uses descriptive qualitative method. The result of the investigation shown that students’ activity and the student’ mastery in cycle II was improved if comparing with cycle I. the results of the data analysis of the reflection scores for cycle I was 61.89 and 72.33 for cycle II, with the 82.22% students’ progress degree in cycle I and 95.56% students’ progress degree in cycle II. While the improving students’ activity who really not active 24.44% became 0%, students’ lack active from 31.11% became 15.56%, students’ active enough from 15.56% became 33.33%, active students’ from 15.56% became 22.22% and super active students’ from 13.33% became 28,89%.Keyword: cooperative learning type Student Teams Achievement Division, learning activity, learning achievement.